Towards SCION-enabled IXPs: The SCION Peering Coordinator - Schulz, Lars-Christian; Hausheer, David (Electronic Communications of the EASST, 2021)
Internet eXchange Points (IXPs) around the world bring thousands of ISPs together to form dense peering fabrics. Since bilateral BGP peering sessions alone would result in large overhead, many IXPs offer route servers enabling the exchange of routing information with the entire peering population over a single multilateral BGP session. Route servers also perform RPKI validation to combat the lack of authentication and security in BGP. SCION is a novel inter-domain routing architecture addressing the security flaws of BGP by replacing it with a security and reliability centric clean-slate approach. We envision that operators of SCION ASes will be just as open to peering at Internet exchanges as they are today with BGP. Moreover, to fully utilize SCION's multipath capabilities SCION AS operators tend to deploy more different AS numbers than in BGP, further increasing the potential number of unique peering links at an IX. Since SCION has no native multilateral peering support, we propose the SCION peering coordinator, an IXP-hosted service automating SCION peering link setup based on per AS policies. As such, the SCION peering coordinator provides an open peering platform similar to BGP route servers to SCION.